2013
DOI: 10.5099/aj130400226
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Tea on Human Health

Abstract: Tea, with its 5,000-year history, is one of the most popular beverages in the world. According to various estimates, over 4 billion people consume tea. This number has increased in recent years due to the widespread marketing of cold tea-based beverages. During the first millennium tea was primarily considered to be medicine rather than an ordinary drink. Over the last few years a large number of epidemiological studies have conclusively proven that tea is beneficial for people with cardiovascular and neurodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 140 publications
0
1
0
Order By: Relevance
“…Wang et al (2006) opined that the decrease in feed intake could be due to the presence of caffeine in LTAE which reduces the level of serum leptin and decreased their appetite for food which in turn had significant reductive effect on weight gain. It could also be due to the presence of catechins and caffeine which are effective promoters of thermogenesis which invariably impacts on the hypothalamus, and fat oxidation, resulting in reduction in body weight gain (Khan and Mukhtar, 2013;Yashin et al, 2013). In human study, it has been shown that green tea helps to reduce obesity when consumed on daily basis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2006) opined that the decrease in feed intake could be due to the presence of caffeine in LTAE which reduces the level of serum leptin and decreased their appetite for food which in turn had significant reductive effect on weight gain. It could also be due to the presence of catechins and caffeine which are effective promoters of thermogenesis which invariably impacts on the hypothalamus, and fat oxidation, resulting in reduction in body weight gain (Khan and Mukhtar, 2013;Yashin et al, 2013). In human study, it has been shown that green tea helps to reduce obesity when consumed on daily basis.…”
Section: Discussionmentioning
confidence: 99%